Ureteroinguinal hernia: an added advantage for laparoscopy in the management of inguinal hernia—a case report - Zain, Mostafa; Kasem, Ossama; Gamal, Mohamed; Tayel, Ahmed; Abouheba, Mohamed (Frontiers in Surgery, 2024)
Different abdominal organs can herniate into the inguinal canal, including the small bowel, colon, appendix, ovaries, and, less commonly, the urinary bladder and fallopian tubes. Herniation of the ureter within an inguinal hernia is a very rare occurrence. To the best of our knowledge, less than 150 cases have been reported in the literature, including only 15 pediatric cases. A 3-month-old boy presented to our clinic with a left inguinal swelling. Ultrasound of the abdomen and pelvis showed grade 4 left hydronephrosis with a dilated tortuous ureter passing through the left inguinal canal. Further investigation revealed that the patient had a left primary obstructing megaureter with a ureteroinguinal hernia. The case was managed with laparoscopic repair of the inguinal hernia and urethrostomy. The current case proves an additional advantage for laparoscopy as it allows proper visualization of the anatomy and identification of atypical hernias, such as ureteroinguinal hernia.